Should All Scorpion Stings be Followed Up in the Intensive Care Unit? - Tutak, Ayse Sahin; Celiker, Meral; Findiki, Huseyin Avni; Karakaya, Bulent; Tutak, Atilla; Uluadag, Oznur (Archives of Clinical and Biomedical Research, 2018)
Aim: In Turkey, as throughout the world, the incidence of scorpion sting cases and the wide-ranging clinical table, extending from local symptoms to death have not been previously estimated. Therefore, through an examination of patients followed up in the Intensive Care Unit (ICU) and the complications, the aim of this study was to evaluate the indications for acceptance of these cases into ICU. Method: A retrospective examination was made of 59 patients admitted to the ICU of Adiyaman Training and Research Hospital because of a scorpion sting between 2013 and 2016. Results: All the patients had a unilateral extremity sting, presented at the Emergency Department within 8 hours and were administered anti-venom. In respect of local or systemic complications, thrombus developed in the proximal of the extremity in only 2 patients. With the exception of these 2 patients, all the other cases were discharged within 2 days without complications. Conclusion: Although the most poisonous scorpion in the world can be found in our region, no case admitted to the ICU in this 3-year period experienced any systemic complications. This is thought to be due to the early presentation at ED within the first 8 hours and that antivenom is produced in our region. In conclusion from this study, it can be recommended that patients with no requirement for the equipment of ICU should not be admitted and patients with local symptoms only should be monitored on the ward.